Railway Wheel and Rail Roughness Analysis - Tomas Lack; Juraj Gerlici (Communications - Scientific letters of the University of Zilina, 2009)
The paper deals with the railway wheel unroundness (out-of-round) analysis and with the rail head roughness analysis. Roughness of the running surfaces is the predominant source of noise of rail bound transport systems today. Reliable measurements of the roughness of rails and wheels are crucial for noise reduction purposes. In the past, the main purpose of measurements was the understanding of corrugation growth and rolling noise generation. Meanwhile, quantitative descriptions have gained considerable importance.